Produção sustentável de bovinos e proteção dos recursos ambientais no Estado de Rondônia - Arcari, Jonnes Alexandre (2010)
Rondônia is a state with a great economic importance. Despite being on the livestock market just 30 years, it has incredibly grown, becoming competitive in domestic and foreign markets. With a bovine flock of more than 11 million heads, the livestock has been a major theme on sustainable development in the region, mainly because the state makes part of the Amazon where the debate about environmental preservation is a topic of debates and concerns. It is fundamental technological investment to promote the intensification of livestock, considering the diversity of climate and the ground found in the state, as well as politics to improve infrastructure, energy, subsidies for purchasing agricultural machinery and inputs, support to the assistance qualified technique so that the transition of the extensive cattle production for systems of intensive and sustainable cattle production occurs. This study aims to evaluate the production of cattle in the state, discussing the environmental impacts that this activity promotes, evaluate the prospects of livestock in Rondônia, and presents proposals to reconcile this increasingly and important activity to the region by promoting sustainable production, preservation and recovery of the environmental.